Analysis of polar motion excitation using C21 and S21 coefficients from GRACE, SLR and hybrid solutions - Nastula, J. (2025)
Hydrological angular momentum (HAM) is used to quantify the effect of mass changes in the continental hydrosphere on variations in polar motion (PM). It plays a key role in understanding the links between Earth system processes and changes in the planet’s rotation. In this study, we analyze HAM time series computed from various Gravity Recovery and Climate Experiment (GRACE) and GRACE Follow-On (GRACE-FO) solutions, satellite laser ranging (SLR) data, as well as hybrid datasets combining SLR. and GRACE/GRACE-FO solutions. Our results show that most HAM series derived from hybrid solutions closely match the hydrological signal observed in geodetic PM excitation (GAO). HAM derived from hybrid solutions generally performs similarly to, or better than the series based on single GRACE/GRACE-FO or SLR. solutions. For seasonal oscillations, the agreement between HAM and GAO is similar for both combined and single-technique solutions, while hybrid datasets show greater consistency in the non-seasonal spectral band. We find strong correlations between GAO and HAM from combined solutions for non-seasonal short-term variations (around 0.6) and non-seasonal long-term variations (around 0.9). These results highlight the significant potential of hybrid data for analyzing PM excitation, especially in the non-seasonal spectral band. The undeniable advantage of hybrid solutions compared to GRACE/GRACE-FO data is their significantly longer observation time series and the fact that their quality does not experience periodic declines as significant as those observed for GRACE/GRACE-FO.